2007
DOI: 10.1007/s11270-007-9546-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Tree Rings and Peat Deposit Geochemical Archives in the Vicinity of a Lead Smelter

Abstract: The content of Pb,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
(57 reference statements)
3
12
0
Order By: Relevance
“…A similar increase in Ca concentrations in spruce trees was also observed by Mihaljevič et al (2008) in the vicinity of the Příbram smelter.…”
Section: Radial Distribution Of Nutrient Elements In Tree Ringssupporting
confidence: 78%
See 1 more Smart Citation
“…A similar increase in Ca concentrations in spruce trees was also observed by Mihaljevič et al (2008) in the vicinity of the Příbram smelter.…”
Section: Radial Distribution Of Nutrient Elements In Tree Ringssupporting
confidence: 78%
“…Comparable patterns in conifers have been found by other authors (e.g. Watmough and Hutchinson 2002;Mihaljevič et al 2008) and may be influenced by differences between sapwood and heartwood chemistry. Similarly to Mg, K concentrations in beech trees were significantly higher than in spruce trees.…”
Section: Radial Distribution Of Nutrient Elements In Tree Ringssupporting
confidence: 61%
“…Even though these values are comparatively fairly low, the fact remains that the trees have absorbed a greater amount of lead during this period. Mihaljevič et al (2008) and other researchers Aznar et al 2008) have found that lead exhibits little mobility between adjacent rings, so that the lead concentrations recorded in the trees are an indication of the year during which it was probably absorbed. In fact, several factors could explain the changes observed in the trees' absorption rates, including variations in the physiological responses of the tree, the edaphic conditions (drainage, pH, etc.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, some elements such as cadmium and zinc are more mobile in soil and tree rings and less reliable for dendrochemical analysis (Padilla and Anderson 2002). However, it should be pointed out that the lead element is scarcely mobile in tree xylem, which significantly reduces radial mobility between adjacent rings (Cutter and Guyette 1993;Mihaljevič et al 2008). It follows that lead is a better indicator of contamination events than other chemical elements such as cadmium or zinc (Hagemeyer and Lohrie 1995).…”
mentioning
confidence: 99%
“…Contamination of soils and biomass in the POR and surrounding area has been studied by numerous authors, e.g., by Rieuwerts et al (1999Rieuwerts et al ( , 2000, Borůvka and Drábek (2004), Suchara and Sucharová (2004), Sucharová and Suchara (2004), Ettler et al (2004Ettler et al ( , 2005, and Mihaljevič et al (2008).…”
Section: Litavka River Contamination By Heavy Metalsmentioning
confidence: 99%